Extent and consequences of inadequate disease control among adults with a history of moderate to severe atopic dermatitis. Issue 2 (13th November 2017) - Wei, Wenhui; Anderson, Peter; Gadkari, Abhijit; Blackburn, Stuart; Moon, Rachel; Piercy, James; Shinde, Shashank; Gomez, Jorge; Ghorayeb, Eric
Abstract: Since control of atopic dermatitis (AD) remains challenging but has not been adequately characterized, the objective of this study was to characterize disease control among patients with a history of moderate to severe AD. Data were from the 2014 Adelphi US AD Disease Specific Programme, a cross‐sectional survey of physicians ( n  = 202) and their patients with history of moderate to severe AD ( n  =   1064, 54% female, 75% white, mean age 40 years). Inadequately controlled AD as rated by the physician was defined as currently flaring; deteriorating/changeable AD; or physician dissatisfaction with current control. The overall inadequate control rate was 58.7% ( n  =   625), which increased with current AD severity and was observed in 53.4% and 83.4% of patients receiving immunosuppressants and systemic corticosteroids, respectively. Relative to controls, inadequately controlled patients had poorer disease‐specific quality of life, higher level of work impairment, greater itch and sleep interference with daily living (all P  <   0.05). Multivariate analysis showed factors significantly associated with inadequate control (all P  <   0.05), including Hispanic race, symptoms on the head/neck or lower limbs, itch and sleep interference with daily living. A limitation of the study was reliance on accuracy of reporting, potential selection bias and cross‐sectional study design. In summary, there was a high rate and substantial impact of physician‐rated inadequately controlled disease among patients with a history of moderate to severe AD, suggesting the need for more effective therapies.